Оценка уровня магния у беременных с учетом психологического компонента гестационной доминанты - Сюсюка, В. Г.; Suzuka, V. G.; Сюсюка, Володимир Григорович (МЕДИ Экспо, 2016)
During investigation of magnesium level of pregnant women with psychological component of gestational dominant different from the optimal type in 64.7% of cases there was deviation from the reference values that is in 2.8 times higher than the appropriate indicator of pregnant women with optimal type of psychological component of gestational dominant.
Estimation of magnesium level of pregnant women regarding condition psychological state
Keywords: тези